2015
DOI: 10.1093/infdis/jiv023
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Encephalitis Vaccine From India Induces Durable and Cross-protective Immunity Against Temporally and Spatially Wide-ranging Global Field Strains

Abstract: CTRI/2011/07/001855.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…In general, these studies have shown that NAb titres are highest against G-II and homologous G-III viruses, followed by G-IV and heterologous G-III viruses, whereas titres against G-I viruses are the lowest, and in some cases below protective levels. 22,[24][25][26][27][28][29] A recent study specifically evaluated the ability of a G-III virus to elicit protective responses in mice, and the ability of human post-vaccinal and acute phase sera to neutralize G-V viruses. The study found that (a) NAb titres in mice immunized with either G-III or G-V virus were higher with homologous viruses but poor against G-V, (b) the SA14-14-2 LAV or the P-3 inactivated vaccines were less protective against G-V virus challenge in mice, and (c) both GMTs and SPRs were poor against G-V virus, intermediate against G-I virus, and highest against G-III virus with both post-vaccinal and acute phase human sera.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 99%
See 4 more Smart Citations
“…In general, these studies have shown that NAb titres are highest against G-II and homologous G-III viruses, followed by G-IV and heterologous G-III viruses, whereas titres against G-I viruses are the lowest, and in some cases below protective levels. 22,[24][25][26][27][28][29] A recent study specifically evaluated the ability of a G-III virus to elicit protective responses in mice, and the ability of human post-vaccinal and acute phase sera to neutralize G-V viruses. The study found that (a) NAb titres in mice immunized with either G-III or G-V virus were higher with homologous viruses but poor against G-V, (b) the SA14-14-2 LAV or the P-3 inactivated vaccines were less protective against G-V virus challenge in mice, and (c) both GMTs and SPRs were poor against G-V virus, intermediate against G-I virus, and highest against G-III virus with both post-vaccinal and acute phase human sera.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 99%
“…179 With an Indian CCDI vaccine, it was shown that about two-thirds of the evaluated subjects carried protective NAb titres for up to at least 18 months. 29 The results on the longevity of responses should be interpreted with caution since the outcome may depend on whether the study was conducted in a non-endemic or an endemic area. Seropositivity rates are known to increase significantly beyond 10-15 years of age in endemic areas, 167,[180][181][182] and an inverse correlation has been observed between an age of >5-6 years and the incidence of JE disease.…”
Section: Longevity Of Protective Responses Induced By Je Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations